(untitled) (The Planet, 2022)
Introduction: Congenital heart disease (CHD) is defined as structural, functional, or positional abnormalities of the heart that are present from birth and can appear at any point after birth or not at all. Congenital heart illnesses are a dynamic set of abnormalities that begin in fetal life and alter significantly during postnatal development, rather than a permanent anatomic abnormality that appears at birth. The majority of congenital cardiac defects appear six weeks after conception, and most defects that are compatible with six months of intrauterine life allow for live delivery. Numerous studies conducted in many places throughout the world have determined that the incidence of congenital cardiac disease is 8-10 per 1000 live births. The incidence of congenital cardiac disorders was estimated to be up to 25/1000 live births in research done at CMH Dhaka. Congenital cyanotic heart disease makes up only about a quarter of all congenital cardiac abnormalities. These days, newborn children with various kinds of congenital cyanotic heart disease are a typical occurrence. Early diagnosis and treatment of newborns with congenital cyanotic cardiac disorders is now a priority for neonatologists and pediatricians. Diagnostic services are also accessible in a number of locations. So, to detect congenital cyanotic heart disease an individual incidence, pattern and clinical profile record from an ideal center of our country is a demand of the time which led to carrying out this study. Aim of the study: The aim of the study was to find out the incidence, pattern, and clinical profile of congenital cyanotic heart diseases in children who are admitted to Combined Military Hospital, Dhaka. Methods: This cross-sectional study was carried out at the Pediatric Cardiology Department of Combined Military Hospital, Dhaka Cantonment, Dhaka, from 1st January 2015 to 31st December 2015. A total of 48 patients were selected among patients with congenital cyanotic heart disease who were admitted to the Combined Military Hospital, Dhaka during the study period. Result: Amongst the 48 patients who were finally analyzed, the incidence of congenital cyanotic heart disease was 4.9 per 1000 hospitalized patients and tetralogy of Fallot was the most common (56%) pattern of congenital cyanotic heart disease, others were transpositions of great vessels, a total anomaly of pulmonary venous return and Ebstein anomaly. Most of the patients presented with bluish discoloration of the skin, and mucus membrane. The majority had cyanosis and murmur. Hundred percent of cases ECHO was abnormal. Maximum patients were male and the mean age was 3.44 ± 3 yrs. The economic status of the families affected the disease process significantly. Conclusion: Incidence of congenital cyanotic heart disease was 4.9 per 1000 hospitalized patients and Tetralogy of Fallot was the commonest cyanotic heart disease with a frequency of 56%, Bluish skin was the commonest symptom 38(79%).